The “Long Papolong” Tradition in Marriages among the Descendants of Kyai in the Villages of Kadur and Palengaan, Pamekasan Regency - Rika Jamiliyah (STAI Miftahul Ula Nganjuk, 2026)
Madura is a region with strong customs and traditions. Most people there believe that the customs and traditions of their region must be upheld, especially those related to marriage. This tradition is still strongly upheld, particularly by religious leaders in Madura. One tradition that remains deeply rooted is the custom of “long papolong,” which is considered essential for maintaining the purity of bloodlines and family honor by marrying children of the same lineage to the children of other religious leaders. The method used in this study was qualitative, involving a literature review and interviews with the community and religious leaders in the Madura region, specifically in the city of Pamekasan. This study aims to understand the social and religious meanings behind the “long papolong” custom and its impact on the current social life of the Madurese people. The results show that the “long papolong” tradition serves as a symbol of the continuity of religious authority and social status that is passed down from generation to generation. The “long papolong” tradition also serves as a means of maintaining solidarity among families of fellow clerics and preserving the moral image associated with the descendants of clerics.